Incidence and Diagnostic Challenges of Bowel Ischemia after Continuous-flow Left Ventricular Assist Device Therapy. Issue 5 (20th August 2021) - Choi, Ashley Y.; Anand, Jatin; Bishawi, Muath; Halpern, Samantha E.; Contreras, Fabian J.; Mendiola, Michelle A.; Daneshmand, Mani A.; Schroder, Jacob N.; Vatsaas, Cory; Agarwal, Suresh M.; Milano, Carmelo A.
Abstract : Long-term continuous-flow left ventricular assist device (CFLVAD) therapy is limited by complications. Compared with stroke and renal dysfunction, post-CFLVAD bowel ischemia is poorly characterized. Adult patients who underwent first-time durable CFLVAD implantation at our institution between 2008 and 2018 were identified and screened for bowel ischemia using Current Procedural Terminology codes for abdominal surgical exploration and International Classification of Disease codes for intestinal vascular insufficiency. Patients who developed biopsy-proven bowel ischemia (cases) were matched to controls (1:1, nearest neighbor, caliper = 0.29) based on preoperative characteristics. Incidences of postoperative right heart failure and renal replacement therapy were compared using McNemar's test. One year survival was estimated using the Kaplan-Meier method. Overall, 711 patients underwent CFLVAD implantation. Nineteen (2.7%) developed bowel ischemia (cases) median 17 days postimplantation (IQR 8–71). The majority of cases were male (78.9%), Black (63.2%), received HeartMate II (57.9%), treated as destination therapy (78.9%), and had a history of hypertension (89.5%), chronic kidney disease (84.2%), hyperlipidemia (84.2%), smoking (78.9%), and atrial fibrillation (57.9%). Post-LVAD, case patients were more likely to develop moderate-severe right heart failure (89.5% vs. 68.4%, p = 0.005), require renal replacement therapy (21.1% vs. 0%, p < 0.001), and less likely to survive to discharge (52.6% vs. 89.5%, p = 0.02) compared with controls. Case subjects demonstrated worse 1 year survival. While less common than stroke and renal dysfunction, post-CFLVAD bowel ischemia is associated with high 1 year mortality. Multi-institutional registries should consider reporting abdominal complications such as bowel ischemia as an adverse event to further investigate these trends and identify predictors of this complication to reduce patient mortality.